Clinical Impact and Economic Burden of Hospital-Acquired Conditions Following Common Surgical Procedures. Issue 22 (15th November 2018) - Horn, Samantha R.; Liu, Tiffany C.; Horowitz, Jason A.; Oh, Cheongeun; Bortz, Cole A.; Segreto, Frank A.; Vasquez-Montes, Dennis; Steinmetz, Leah M.; Deflorimonte, Chloe; Vira, Shaleen; Diebo, Bassel G.; Neuman, Brian J.; et al.
Abstract : Study Design: Retrospective review of prospectively collected data. Objective: To assess the clinical impact and economic burden of the three most common hospital-acquired conditions (HACs) that occur within 30-day postoperatively for all spine surgeries and to compare these rates with other common surgical procedures. Summary of Background Data: HACs are part of a non-payment policy by the Centers for Medicare and Medicaid Services and thus prompt hospitals to improve patient outcomes and safety. Methods: Patients more than 18 years who underwent elective spine surgery were identified in American College of Surgeons' National Surgical Quality Improvement Program (ACS-NSQIP) database from 2005 to 2013. Primary outcomes were cost associated with the occurrence of three most common HACs. Cost associated with HAC occurrence derived from the PearlDiver database. Results: Ninety thousand five hundred fifty one elective spine surgery patients were identified, where 3021 (3.3%) developed at least one HAC. Surgical site infection (SSI) was the most common HAC (1.4%), then urinary tract infection (UTI) (1.3%) and venous thromboembolism (VTE) (0.8%). Length of stay (LOS) was longer for patients who experienced a HAC (5.1 vs. 3.2 d, P  < 0.001). When adjusted for age, sex, and Charlson Comorbidity Index, LOS was 1.48 ± 0.04 days longer ( P  < 0.001) and payments were $8893 ± $148 greater ( P  < 0.001) for patients with at least one HAC. With the exception of craniotomy, patients undergoing common procedures with HAC had increased LOS and higher payments ( P  < 0.001). Adjusted additional LOS was 0.44 ± 0.02 and 0.38 ± 0.03 days for total knee arthroplasty and total hip arthroplasty, and payments were $1974 and $1882 greater. HACs following hip fracture repair were associated with 1.30 ± 0.11 days LOS and $4842 in payments ( P  < 0.001). Compared with elective spine surgery, only bariatric and cardiothoracic surgery demonstrated greater adjusted additional payments for patients with at least one HAC ($9975 and $10, 868, respectively). Conclusion: HACs in elective spine surgery are associated with a substantial cost burden to the health care system. When adjusted for demographic factors and comorbidities, average LOS is 1.48 days longer and episode payments are $8893 greater for patients who experience at least one HAC compared with those who do not. Level of Evidence: 3 Abstract : Supplemental Digital Content is available in the text